What you don't know AI's unseen influence on your life and how to take back control - Abercrombie, Cortnie (Ascent Audio, 2022)
You are probably not aware, because of their hidden nature, but artificial intelligence systems are all around you affecting some of the biggest areas of your life-jobs, loans, kids, mental health, relationships, freedoms, and even healthcare decisions that can determine if you live or die. As an executive working in AI at one of the largest, most sophisticated tech companies on the planet, Cortnie Abercrombie saw firsthand how the corporate executives and data science teams of the Fortune 500 think about and develop AI systems. In this book she makes it easy to understand how AI works and unveils what companies are doing with AI that can impact you the most. Most importantly, she offers practical advice on what you can do about it today and the change you should demand for the future.
Online resource; title from title details screen (O'Reilly, viewed May 3, 2022)
Keywords: Artificial intelligence -- Social aspects; Intelligence artificielle; Aspect social; Artificial intelligence; Social aspects; Downloadable audio books; Audiobooks; Livres audio